Parameters for safe dissection at Calot's Triangle in Laparoscopic Cholecystectomy - Anmar Hamid Hamad; Ghassan Ali Al-Kizwini (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the parameters critical to safe laparoscopic cholecystectomies. Method: The prospective study was conducted at Al-Yarmook Teaching Hospital, Baghdad, from May 1, 2020, to December 31, 2021, and comprised patients with gall-stone disease who were admitted for laparoscopic cholecystectomy. Consecutive non-probability sampling technique was used for collecting the data which was analysed using SPSS (version 25). Results: Of the 93 patients, 68(73.12%) were females, and 25(26.88) were males. The overall mean age was 40.7±8.1 years, and 52(55.91%) patients were aged >40 years. Calot triangle was seen in 72(77.4%) cases, while the sulcus of Rouviere, duodenum and right hepatic artery were spotted in 50(53.8%), 49(52.7%) and 19(20.4%) cases, respectively. There was a significant association of late presentation, lateral traction, 4-port option, good setting and difficult anatomy with anatomical landmark visualisation (p<0.05). Conclusions: There is a need for a national guideline to ensure safe laparoscopic cholecystectomy. Key Words: Cholecystectomy, Laparoscopic, Hepatic Artery, Traction, Duodenum